1997
DOI: 10.1111/j.1528-1157.1997.tb01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Unexplained Death in Epilepsy: Observations from a Large Clinical Development Program

Abstract: Summary:Purpose: The present study was conducted to determine the rate of sudden unexplained death in epilepsy (SUDEP) in a well-defined cohort of patients included in the lamotrigine (LTG) clinical development database.Methods: A panel of scientists experienced in the area of SUDEP was assembled and provided with case summaries on all deaths (n = 45) reported during the initial clinical development of LTG. The panel developed a set of criteria for classifying cases as SUDEP (definite or highly probable), poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
151
4
10

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(169 citation statements)
references
References 18 publications
4
151
4
10
Order By: Relevance
“…Terrence et al, in a comparable study, reported a figure of 32 years 4 . Leestma et al reported a mean age of death of 28 years 10 . The two peak decades of SUDEP in our study were the third and fourth decades, while in Terrence s study the second and fifth decades were the highest 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Terrence et al, in a comparable study, reported a figure of 32 years 4 . Leestma et al reported a mean age of death of 28 years 10 . The two peak decades of SUDEP in our study were the third and fourth decades, while in Terrence s study the second and fifth decades were the highest 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Following this reasoning, postmortem examinations in people dying of SUDEP have found hearts that are dilated and heavier than expected 16,29,31,32 and pulmonary edema in approximately 50-86% of cases 16,26,29,32,33 . Furthermore, others have described pathological changes in the hearts of those dying with SUDEP, including fibrosis of the walls of small coronary arteries, atrophy of cardiomyocytes, myofibrillar degeneration, edema of the conductive tissue and morphological abnormalities of the cardiac conduction system 26,29,31,34,35 .…”
Section: Sudden Unexpected Death In Epilepsymentioning
confidence: 97%
“…Comparisons of incidence estimates for SUDEP are difficult, since different definitions of SUDEP have been used, not all patients have a postmortem examination, and case ascertainment methods and source populations have varied 15 . The incidence of SUDEP has been estimated to be 3.5/1000 person-years in a lamotrigine clinical trial 16 , 0.5-1.4/1000 person-years in people with treated epilepsy 17 , 5.9/1000 person-years in outpatients with epilepsy at a tertiary referral centre 18 and 0.35/1000 person-years in a population-based study 19 . The National General Practice Study of Epilepsy (NGPSE), a community-based study in the United Kingdom, saw the first case of SUDEP after 11,000 person-years of follow-up 20 , and the results of the Medical research Council Antiepileptic Drug withdrawal Study showed that SUDEP is a rare event among patients with epilepsy in remission 21 .…”
Section: Sudden Unexpected Death In Epilepsymentioning
confidence: 99%
See 2 more Smart Citations